ChemInform Abstract: SiO2—H3BO3 Promoted Solvent‐Free, Green and Sustainable Synthesis of Bioactive 1‐Substituted‐1H‐tetrazole Analogues. Issue 29 (July 2015) - Parveen, Mehtab; Ahmad, Faheem; Mohammed Malla, Ali; Azaz, Shaista
Abstract Multi‐functionalized title compounds (III) are synthesized by condensation of various heterocyclic/aromatic primary amines (I), sodium azide, and triethyl orthoformate (II) without use of an environmentally toxic solvent.